A comparative study of evapotranspiration in riparian zone under coniferous and deciduous forest covers using groundwater table fluctuations: a case study in the Kiskatinaw River Watershed, Canada. (2015) - Saha, Gopal Chandra
Shallow groundwater in riparian zone influences evapotranspiration (ET) by interacting with soil, vegetation and climate through water table fluctuation. In this study, monthly and seasonal trends of ET under coniferous and deciduous forest covers were investigated using field observed groundwater table (GWT) data in the Kiskatinaw River Watershed, Canada. One piezometer equipped with data logger was installed in each forest cover which is separated by a stream and continuous measurement of GWT was implemented in every 15 minutes in both piezometers from December 2010 to January 2011 and April 2011 to November 2011. The field data indicated that GWT fluctuate substantially almost every month in both forest covers during the monitoring period. These GWT data were then used to estimate monthly and seasonal ET. The monthly and seasonal trends of ET were variable in both forest covers due to variable GWT fluctuations. The results were also influenced by precipitation and temperature. The findings from this study are helpful for efficient seasonal water resources management plan by compromising the change of different forest covers and considering seasonal variability of ET depending on future water demands.